Chloride Permeability and Sulfate Resistance of Concrete Incorporating Waste Foundry Sand - Singh, Jagdeep (My University, 2018)
Concrete deterioration due to external sulfate attack is prevalent matter in costal areas and even now it occurs in non costal areas due to industrialization and modern agricultural practise which cause water contamination and thus lead to concrete deteriorate as in case of sulfate attack. So its high time to find concrete containing some waste materials which should be sulfate resistant. In this way three problems can be cured with single concrete, one waste management, secondly reduce over-exploitation of natural resources (sand, cement and coarse aggregates) and thirdly sulfate durability. So to achieve the above scenario study on waste foundry sand used as fine aggregate replacement material in concrete under external sulfate attack was done in the thesis. The comparative study done on concrete containing waste foundry sand as 5%, 10%, 15% and 20% of fine aggregate replacement by weight in 10% sodium sulfate solution and in normal water. To determine sulfate attack mainly three test conducted up to 56 days curing age are compressive strength, mass loss and length change, along with this Chloride ion permeability (RCPT) and ultrasonic pulse velocity (USPV) are also done to just correlate them with sulfate durability property of concrete. No loss in mass and compressive strength observed. Increase in compressive strength (1.0% to 22.2%) is more in case of water curing as compare to sodium sulfate curing. Increase in mass (2% to 90%), pulse velocity (0% to 0.92%)and decrease in charge (1% to 35%) in case of sodium sulfate curing is higher as compare to water curing concrete. SEM-XRD analysis also indicate some traces of sulfate attack in concrete. Increase in strength due to WFS and no major damage observed in concrete due to sodium sulfate curing so it can be used in sulfate environment also.
Master of Engineering- Structures
Keywords: Waste Foundry Sand; Chloride Permeability; Sulfate Resistance; Durability Property